2003
DOI: 10.1002/hyp.1243
|View full text |Cite
|
Sign up to set email alerts
|

Sediments, porewaters and diagenesis in an urban water body, Salford, UK: impacts of remediation

Abstract: Abstract:Contaminated sediments deposited within urban water bodies commonly exert a significant negative effect on overlying water quality. However, our understanding of the processes operating within such anthropogenic sediments is currently poor. This paper describes the nature of the sediment and early diagenetic reactions in a highly polluted major urban water body (the Salford Quays of the Manchester Ship Canal) that has undergone remediation focused on the water column.The style of sedimentation within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
7
0
3
Order By: Relevance
“…Early diagenetic sulphide mineral precipitates have been documented previously to act as sinks for trace metals in marine and brackish sediments (Parkman et al, 1996;Pirrie et al, 1999;Morse and Luther, 1999) and these minerals are routinely considered in contaminated marine sediment assessment (Ankley et al, 1996). Our study is the first to consider the incorporation of the potentially toxic element Zn in vivianite, an important mineral in anoxic environments such as acid mine drainage sites (Ueshima et al, 2004), rivers (House, 2003), lakes (Fagel et al, 2005) and urban water bodies (Taylor et al, 2003). There is a need to study the role of vivianite in the uptake of other potentially toxic elements in freshwater systems (e.g.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Early diagenetic sulphide mineral precipitates have been documented previously to act as sinks for trace metals in marine and brackish sediments (Parkman et al, 1996;Pirrie et al, 1999;Morse and Luther, 1999) and these minerals are routinely considered in contaminated marine sediment assessment (Ankley et al, 1996). Our study is the first to consider the incorporation of the potentially toxic element Zn in vivianite, an important mineral in anoxic environments such as acid mine drainage sites (Ueshima et al, 2004), rivers (House, 2003), lakes (Fagel et al, 2005) and urban water bodies (Taylor et al, 2003). There is a need to study the role of vivianite in the uptake of other potentially toxic elements in freshwater systems (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…1). A full description of this site, 4 and its contamination and remediation history, can be found in Taylor et al (2003). The Manchester Ship Canal is up to 8 m deep, steep-sided and up to 50 m wide.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Within contaminated sediments, metals commonly co-precipitate with Fe and Mn oxides. The chemical reduction of these oxides results in the release of these adsorbed contaminants to sediment porewaters (Dodd et al 2003;Taylor et al 2003) and thence to overlying water. The build-up of chemical species in sediment porewaters also leads to the precipitation of authigenic minerals in the sediment.…”
Section: Urban Canals and Docksmentioning
confidence: 99%
“…It was shown that resuspension, through relations between particle flux and hydrodynamics, can be either the fact of dynamics of the introduction system or that of the chalk karstic aquifer.Bravo-Espinosa et al (2003) evaluated conditions of bedload transport using hydraulic, sediment, land-use, and rock-erosivity data of 22 alluvial streams. The study also looked at the performance of selected bedloadtransport equations Taylor et al (2003). examined the nature of sediment, porewaters and diagenesis in a highly polluted urban water body, the Salford Quays, UK, and the impacts of remediation.…”
mentioning
confidence: 99%